R. S. Williamson correspondence - Williamson, R. S. (Robert Stockton), 1824-1882.
Letters (1848 January 21-1854 April 1) from Williamson to members of his family relating chiefly to his experiences as a lieutenant in the Army Corps of Topographical Engineers in California during the gold rush period.
Army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States. -- Army. -- Corps of Topographical Engineers; Military topography -- California; California -- Gold discoveries; Army officers